Effects of creatine loading on muscular strength and endurance of female softball players - Ayoama, R.; Hiruma, E.; Sasaki, H. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The purpose of this study was to determine the effects of Cr supplementation on muscle strength and endurance of the trained females, the effect of anaerobic exercises performed before the supplementation and disappearance of the effects on the performance. Methods: Twenty-six collegiate female softball players were divided into the Cr1, 2, Control (Cont.)1 or 2 group, randomly. They performed maximal 2-isometric and 30-isokinetic knee extensions at the angular velocities of 180° and 60°/s. Thereafter, the subjects of the Cr2 and Cont.2 groups performed resistance exercises with 10 RM and cycling with 0.01 kg . kg-1 body weight, alternately during the 1st week. During the 2nd week, the subjects of the Cr1 and 2 groups ingested 20 g Cr a day for 1 week. Thereafter, the subjects in the Cr2 group continued 3 g Cr ingestion a day for 2 weeks while the Cr1 group ingested the same amount of placebo during the 3rd and 4th weeks. The subjects of the Cont.1, 2 groups ingested the same amount and taste of placebo during the 1st to 4th weeks. This study was undergone in double blind fashion. The similar measurements, to which the subjects performed the 1st day, were carried out on the final day of the 2nd, 3rd and 4th weeks. Results: Though maximal isometric strength did not differ in intra- and intergroups, the isokinetic peak torque in the Cr1 group was significantly decreased in the 4th measurement (p<0.01). The mean torque of the 1st to 10th knee contractions at 60°/s was significantly decreased from the 2nd measurement in the Cont.1, 2 groups, compared with that in the 1st measurement (p<0.01). In the Cr groups, the significant decrease was detected from the 3rd in the Cr1 and in the 4th measurement in the Cr2 group. The mean torque of the latter 20 contractions at 180°/s was significantly increased in the Cr2 group (p<0.001). In the 1st measurement, the mean torque in the Cr1 group was significantly higher than that in the Cr2 group (p<0.05). However, the differences between Cr1 and 2 groups were not detected from the 2nd measurement. Conclusion: Twenty g Cr supplementation a day for a week to the trained females improves not the maximal static strength and dynamic peak torque but the mean strength and endurance of repeated contractions. However, the effects on females are not so great as that ever found in males. The effects are enhanced by anaerobic exercises performed before the supplementation and would disappear in a week if the supplementation were stopped.